Economical running strategy for East African distance runners - Ishikawa, M.; Sano, K.; Kunimasa, Y.; Oda, T.; Nicol, C.; Ito, A.; Komi, P. V. (The Journal of Physical Fitness and Sports Medicine, 2013)
The superior success of East-African endurance runners has stimulated a large amount of interest in exploring valid reasons for their performance, especially for neuromuscular mechanics. This review provides a brief overview of classic neuromuscular interaction during running; and, thereafter, describes a specific neuromuscular interaction alternative to the classic stretch-shortening cycle concept for enhancing the running economy of East-African distance runners.